ANALISIS PERJANJIAN PERKAWINAN DAN AKIBATNYA MENURUT UNDANG-UNDANG PERKAWINAN DI INDONESIA - Muhammad Sopiyan (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2023)
Marriage is an agreement made by two people, in terms of, This is an agreement between a man and a woman with a material goal, namely forming a happy and eternal family (household) based on Belief in One Almighty God, as the first principle in Pancasila. In a marriage carried out one of them will give birth to the effects of marriage on assets. As situations and conditions develop in society, many potential partners finally decide to enter into a marriage agreement, bearing in mind that this is because both men and women are capable of producing their respective assets and there are many other reasons why they should enter into a marriage agreement. A marriage agreement is an agreement made by two people (prospective husband and wife) before the marriage takes place. The marriage agreement has been regulated in Article 29 of the Marriage Law No. 1 of 1974 but with the issuance of the Constitutional Court decision No. 69/PUU-XIII/2015 there have been several changes in the Marriage Agreement which are currently still Pros and Cons in society. The problems examined in this study are: how is the marriage agreement viewed from the Civil Code. As for the analysis of legal materials in this study, it is carried out by processing and analyzing qualitatively and as outlined descriptively. The results of the research in the first conclusion that the regulation of marriage agreements in Indonesia is contained in several laws including the Civil Code, Marriage Law No. 1 of 1974, KHI and Constitutional Court Decision No. 69/PUU-XIII/2016.